Improving audit reports: A consensus between auditors and users - Estibaliz Goicoechea; Fernando Gómez-Bezares; José V. Ugarte Susaeta (International Journal of Financial Studies, 2021)
Audit reports represent the only information stakeholders have about conducted audits and they are a key instrument used in economic and financial decisions. Improving audit reports should be a priority of regulators and auditors. The authors solicited perceptions from 212 experienced auditors and financial report users about the value of audit reports and ways to improve their format and content. An analysis of the responses suggests that adding information on audits (such as auditor's responsibility about fraud) and on annual accounts and client's information systems, without significant changes in the format, would improve the decision usefulness of audit reports. The growing sophistication of markets and reporting standards requires new information in audit reports, such as auditors' conclusions about management's estimates in annual accounts. The study is useful to regulators, auditors' corporations, academics, and users and contributes to the current audit literature by providing evidence on consensus between auditors and users with regard to the format and content of audit reports.
Keywords: 330; audit report; consensus between auditors and users; information value for decision making